The effect of baby massage and baby spa on weight gain in 3-9 month-old babies at Mahanum Clinic - Fauziah, Yaumil; Nasution, Yulia Fatma; Sitorus, Nopita Yanti; Lubis, Desi Handayani; Nasution, Annisa Namirah; R, Maimunah (Institute of Computer Science (IOCS), 2025)
Child developmental disorders occur when genetic or environmental factors fail to meet a child's basic growth and development needs. Prompt detection and appropriate intervention can help improve the quality of a child's growth and development later in life. This study aimed to determine the effect of infant massage and baby spa treatments on weight gain in infants aged 3 to 9 months. This was a quasi-experimental study using a pre-test-post-test with a control group design. The subjects consisted of 20 infants in the case group and 20 infants in the intervention group at Mahanum Clinic. The results showed that the average weight gain in infants aged 3-9 months in the intervention group was 740.48 grams, while the average weight gain in the control group was 206.48 grams. The results of the Paired Sample T-test showed a p-value of 0.000 < 0.05, indicating that both baby spa and baby massage have an effect on the weight of babies aged 3-9 months. The results of the Independent T-test showed a p-value of 0.004 < 0.05, indicating that there is a significant difference between baby spa and baby massage on the weight of babies aged 3-9 months, with baby spa being superior to baby massage. It is recommended that midwives use baby spa as an appropriate health promotion strategy to increase infant weight.